A dichotomous key to the genera of the Marine Heterotardigrades (Tardigrada) - Fontoura, Paulo; Bartels, Paul J.; Jørgensen, Aslak; Kristensen, Reinhardt Møbjerg; Hansen, Jesper Guldberg (Zootaxa, 2017)
This is an identification guide to the 47 currently described genera of marine heterotardigrades. We provide clear definitions and illustrations of relevant anatomy and an easy to use dichotomous key. The aim of the present contribution is to enable more people to identify collected specimens of marine heterotardigrades, and hopefully, encourage more people to study this intriguing group of animals. The paper is divided into three parts. The first part gives a brief introduction to heterotardigrade morphology with special emphasis on taxonomically important characters. The second part is the actual key, which is accompanied by illustrations of both habitus and detailed foot morphology of the marine heterotardigrade genera. The third part provides up to date diagnoses of the orders, families, subfamilies and genera of marine heterotardigrades according to the most recent emendments. With the generic diagnoses, we provide a bibliography with selected literature that relates to each specific genus.